Fractionation of the major whey proteins and isolation of β-Lactoglobulin variants by anion exchange chromatography - Santos, Maria João (2012)
A method for the separation and fractionation of the major whey proteins from a whey protein concentrate (WPC80) by anion-exchange chromatography coupled to a Fast Protein Liquid Chromatography (FPLC) system is proposed. The method is based on the use of an ionic column (Mono Q) and a salt gradient elution by increasing the ionic strength of the elution buffer (Tris–HCl 20 mM plus 0 to 1 M NaCl). The proposed method was found to be suitable to fractionate the major whey proteins from the WPC80 in different fractions, namely one fraction containing all the a-Lactalbumin and immunoglobulins; another fraction containing all the bovine serum albumin; and two distinct fractions each containing a different variant of b-Lactoglobulin. A 60.5% (w/w) recovery of the two main b-Lactoglobulin variants was obtained.